(untitled) (Journal of Parents and Teachers, 2026)
Francisco Reus responds to a letter from a former student who criticises his teaching methods. The author acknowledges that teachers also make mistakes, but defends his work as an educational mission that seeks to instil habits, values and responsibility. His intention was never to exercise authority, but rather to encourage effort and reflection in his students.